Mapping women's empowerment : experiences from Bangladesh, India, and Pakistan - Azim, firdous; Sultan, Maheen (Dhaka : University, 2010)
Papers presented at the Scoping Workshop of the South Asia Hub of the Women's Empowerment Programme sponsored by BRAC University, held from August 18-21, 2006 in Dhaka.
Includes index and bibliographycal references
Keywords: Women in development -- Bangladesh -- Congresses; Women in development -- India -- Congresses; Women in development -- Pakistan -- Congresses